2004
DOI: 10.1021/la0363938
|View full text |Cite
|
Sign up to set email alerts
|

Two Phase Transitions of Poly(N-isopropylacrylamide) Brushes Bound to Gold Nanoparticles

Abstract: The thermally induced phase transition of the poly(N-isopropylacrylamide) (PNIPAM) brush covalently bound to the surface of the gold nanoparticles was studied using high-sensitivity microcalorimetry. Two types of PNIPAM monolayer protected clusters (MPCs) of gold nanoparticles were employed, denoted as the cumyl- and the cpa-PNIPAM MPCs, bearing either a phenylpropyl end group or a carboxyl end group on each PNIPAM chain, respectively. The PNIPAM chains of both MPCs exhibit two separate transition endotherms; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
209
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(240 citation statements)
references
References 20 publications
30
209
1
Order By: Relevance
“…The first transition peak is relatively sharp and narrow, while the second is markedly broader. The same observation was reported by Tenhu and coworkers 28 and Liu and coworkers. 29 Reasonably, the first endothermic peak should be attributed to the collapse of PNIPAAm segments in the vicinity of hydrophobic PCL aggregate, whereas the second should be attributed to the collapse of relatively free PNIPAAm segments in the outlying block.…”
Section: Phase Transitionsupporting
confidence: 87%
“…The first transition peak is relatively sharp and narrow, while the second is markedly broader. The same observation was reported by Tenhu and coworkers 28 and Liu and coworkers. 29 Reasonably, the first endothermic peak should be attributed to the collapse of PNIPAAm segments in the vicinity of hydrophobic PCL aggregate, whereas the second should be attributed to the collapse of relatively free PNIPAAm segments in the outlying block.…”
Section: Phase Transitionsupporting
confidence: 87%
“…This makes them particularly interesting for controlled release, 7 tunable assembly of coated nanoparticles, 8 responsive nanoactuators 9,10 or for antifouling surfaces. 11,12 More recently, complex systems produced by embedding surfactants, 13,14 gels 15,16 or nanoparticles [17][18][19][20] into polymer brushes have been studied, from which multiresponsive coatings with enlarged applicability as stimuli-responsive systems can be designed. Among them, there are some examples of polyelectrolyte (PE) chains adsorbed onto charged polymer brushes.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers also have reported the preparation of PIPAAm brush by ATRP. Balamurugan et al [31] and Shan et al [32] independently prepared PIPAAm brush surfaces on gold and investigated thermoresponsive hydration transition behavior. Xu et al [33] prepared PIPAAm brush surfaces on silicon and observed 3T3 adhesion/detachment behavior according to the temperature changes.…”
Section: Introductionmentioning
confidence: 99%